Outsiders, outcasts, and outlaws: postmodernism and rock music as countercultural forces in Salman Rushdie's The ground beneath her feet - Hutt, Dan (Kansas State University, 2011)
Salman Rushdie's 1999 novel The Ground Beneath Her Feet is ostensibly a rock 'n' roll novel, largely set in the 1960s, that traces the commercial rise of Indian rock star protagonists Vina Apsara and Ormus Cama. As their fame and wealth rise to global status and their stage show comes to entail a logistical complexity of military proportions, it becomes increasingly difficult to discern the couple's earlier countercultural ideals within their new established culture status. I argue that despite the change from countercultural to establishment-based values in the novel's protagonists, Rushdie does make a case in The Ground Beneath Her Feet for the possibility of countercultural efficacy against the commodifying culture of global capitalism (which I refer to as the "Frame"). His recipe for combating the exclusive hierarchies produced by the Frame is a combination of the non-totalizing politics of postmodernism and the subversive potential of uncommodified rock music. I pay close attention to establishing the historical templates--John Lennon of the Beatles and Brian Wilson of the Beach Boys--of the novel's protagonists in an effort to understand the sort of countercultural alternative Rushdie is proposing. I likewise focus on the novel's depiction of the Beach Boys' Smile album, which as a still commercially unreleased record, reinforces Rushdie's imperative in The Ground Beneath Her Feet for an uncommodifying counterculture and works in tandem with his portrayals of the artistic plights of several minor characters in the novel as well.
Keywords: Salman Rushdie; The Ground Beneath Her Feet; Counterculture; Smile; Brian Wilson; Rock novel; Literature (0401); Music (0413)